2008
DOI: 10.1002/mame.200800158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clay Modification on the Properties of Resol Nanocomposites

Abstract: Two organically modified (Cloisite® 30B and 10A) and one unmodified clay (Cloisite® Na) were added to a resol‐type phenolic prepolymer. The modified montmorillonites showed a better dispersion in the prepolymer. The dispersion of the clay, the chemical structure as well as the thermal degradation behavior of the cured polymer and nanocomposites were studied. It was observed that the addition of Cloisite® Na leads to enhanced crosslinking of the cured polymer, leading to a higher activation energy for thermal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…[ 16 ] It was found that the addition of clays with modifi ers containing hydrophilic groups led to less crosslinked polymer networks than in the case of the resol, because of the interaction between the modifi er and the prepolymer. However, a strong intercalation of the resol into the montmorillonite galleries and subsequent exfoliation lead to an increase of the hardness and elastic modulus of the nanocomposite.…”
Section: Research Newsmentioning
confidence: 99%
“…[ 16 ] It was found that the addition of clays with modifi ers containing hydrophilic groups led to less crosslinked polymer networks than in the case of the resol, because of the interaction between the modifi er and the prepolymer. However, a strong intercalation of the resol into the montmorillonite galleries and subsequent exfoliation lead to an increase of the hardness and elastic modulus of the nanocomposite.…”
Section: Research Newsmentioning
confidence: 99%
“…It was stated that the experimental conditions as well as the surfactant selected to compatibilize the clay with the polymer and the intrinsic properties of the polymer are crucial to control the dispersion. The aim of this work is to obtain phenolic/MMT nanocomposites synthesized by in situ polymerization maintaining similar conditions of synthesis and curing than those used in a previous work 15. Although in the previous work the resol nanocomposite was obtained by intercalation of the prepolymer, in this study, in situ polymerization was used.…”
Section: Introductionmentioning
confidence: 99%
“…Different ways of synthesis were used to obtain nanocomposites based on clay and phenolic resins, both novolacs and resols. It was reported the synthesis of phenolic resins by melt intercalation,5–9 in situ polymerization,10–13 and intercalation of prepolymer 14, 15. In those works, different conditions of synthesis and curing, formaldehyde to phenol molar ratio, type of clay, and organic modifiers were used.…”
Section: Introductionmentioning
confidence: 99%
“…As for the modified montmorillonite, the more hydrophobic it became, the worse the compatibility with the polymer. Therefore, it can be noticed in case of Cl30B, Cl20A and Cl15A agglomerates of clay layers [22,23] within the polymeric structure.…”
Section: Scanning Electron Microscopy and Transmission Electron Micromentioning
confidence: 97%